Long-term creep properties of Ni-based 21Cr-18Fe-9Mo superalloys - Kota Sawada; Yasushi Taniuchi; Kaoru Sekido; Takehiro Nojima; Tomotaka Hatakeyama; Kazuhiro Kimura (Science and Technology of Advanced Materials: Methods, 2023)
ABSTRACTTensile properties and creep rupture strength were evaluated for Ni-based 21Cr-18Fe-9Mo superalloy plate and bar products used for gas turbines. Tensile tests at room temperature to 1000°C and creep tests at 700°C to 1000°C were performed in accordance with JIS G 0567 and JIS Z 2271, respectively. The creep strength of the plate (iHA) was slightly higher than that of the bars (iHB and iHC) in the short term. However, the difference in the creep strength became small in the long term. Regression analysis was performed for the tensile test data of each product form. The creep rupture data of the plate and bar products were separately fitted to the regression equation of logarithmic stress using the time – temperature parameters of Larson – Miller, Orr – Sherby – Dorn, and Manson – Haferd to estimate the 100,000 h creep rupture strength. It was considered that the Manson – Haferd parameter and regression equation of the fourth degree were appropriate for plate and bar products based on the fitting accuracy and simplicity of the regression equation. The value of 67% for the average 100,000 h creep rupture strength at 700°C to 900°C was compared with the allowable stress of the 2021 ASME Code.